Contaminations of Radioactive Nuclides of 238U, 232Th, and 40K in Tin Ore - Salama, Tarek Mohamed Talaat (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Tin ore plays a vital role in several industries. Tin ore could contain natural radioactive nuclides of 238U, 232Th, and 40K with various concentrations which might be caused a significant exposure radiation levels to the workers who handle the Tin ore in the factory. Thus, the evaluation of natural radioactive nuclides 238U, 232Th, and 40K in the Tin ore is important from the point of view of radiation protection to save the workers from the radiation hazards.